A juvenile cf. Edmontosaurus annectens (Ornithischia, Hadrosauridae) femur documents a poorly represented growth stage for this taxon - Farke, Andrew; Yip, Eunice (Vertebrate Anatomy Morphology Palaeontology, 2019)
A nearly complete, but isolated, femur of a small hadrosaurid from the Hell Creek Formation of Montana is tentatively referred to Edmontosaurus annectens. At 28 cm long, the element can be classified as that from an “early juvenile” individual, approximately 24 percent of the maximum known femur length for this species. Specimens from this size range and age class have not been described previously for E. annectens. Notable trends with increasing body size include increasingly distinct separation of the femoral head and greater trochanter, relative increase in the size of the cranial trochanter, a slight reduction in the relative breadth of the fourth trochanter, and a relative increase in the prominence of the cranial intercondylar groove. The gross profile of the femoral shaft is fairly consistent between the smallest and largest individuals. Although an ontogenetic change from relatively symmetrical to an asymmetrical shape in the fourth trochanter has been suggested previously, the new juvenile specimen shows an asymmetric fourth trochanter. Thus, there may not be a consistent ontogenetic pattern in trochanteric morphology. An isometric relationship between femoral circumference and femoral length is confirmed for Edmontosaurus. Overall ontogenetic trends in the femur of Edmontosaurus are concordant with patterns seen in other Hadrosauridae, supporting a fairly conserved pattern of development for this element within the clade.